Effects of a Tai Chi rehabilitation program implemented using a hybrid online and offline mode on oxidative stress and inflammatory responses in patients with coronary heart disease: a randomized controlled trial - Cui, Meize; Wei, Qiuyang; Li, Yameng; Liu, Mingyu; Sun, Ligang; Liu, Xinyi; Chen, Zaihao; Fang, Hui; Liu, Linli; Fu, Jiahao; Li, Cuihan; Li, Haojie; et al. (Frontiers in Public Health, 2024)
Background Coronary heart disease (CHD) is the leading cause of death in both developed and many developing countries. Exercise training is a fundamental component of cardiac rehabilitation programs for patients with CHD. This study aims to investigate the effects of a Tai Chi rehabilitation program, which is provided through a hybrid online and offline mode, on oxidative stress and inflammatory responses in patients with CHD. Methods A total of 34 patients with coronary heart disease were randomly assigned to two groups: an experiment group (n = 14, age 62.07 ± 9.076 years) and a control group (n = 20, age 61.90 ± 9.700 years). The experiment group underwent a 12-week Tai Chi cardiac rehabilitation program (TCCRP), while the control group followed a conventional exercise rehabilitation program (CERP) consisting of 1-h sessions, 3 times per week, for a total of 36 sessions. Participants were studied at baseline and post-intervention. The main assessments include the levels of Malondialdehyde (MDA), Superoxide dismutase (SOD), Tumor necrosis factor (TNF-α) and Interleukin-10 (IL − 10) in blood samples. Pearson correlation analysis was used, and the differences between the two groups were subsequently tested using two-way repeated ANOVA. Statistical significance was defined as a two-sided p-value of <0.05. Results The key finding of the study reveals that MDA was significantly reduced by 1.027 nmoL/mL. Additionally, the TCCRP showed significant improvements in SOD and IL-10, with values of 10.110 U/mL and 2.441 pg./mL, respectively. Notably, a significant positive correlation was found between SOD and IL-10 (r = 0.689, p = 0.006), while MDA showed a significant positive correlation with TNF-a (r = 0.542, p = 0.045). In contrast, the ECRP group only showed a significant improvement in SOD. Conclusion The study conducted a 12-week program on TCCRP, which utilized a hybrid online and offline model for individuals with coronary heart disease. The program showed promising results in alleviating oxidative stress and inflammation, possibly by regulating the balance between oxidative and antioxidative factors, as well as pro-inflammatory and anti-inflammatory factors.